ErbB4 tyrosine kinase inhibition impairs neuromuscular development in zebrafish embryos - Paatero I; Veikkolainen V; Mäenpää M; Schmelzer E; Belting HG; Pelliniemi LJ; Elenius K (My University, 2022)
Tyrosine kinase inhibitors are widely used in the clinic, but limited information is available about their toxicity in developing organisms. Here, we tested the effect of tyrosine kinase inhibitors targeting the ErbB receptors for their effects on developing zebrafish ( Danio rerio) embryos. Embryos treated with wide-spectrum pan-ErbB inhibitors or erbb4a-targeting antisense oligonucleotides demonstrated reduced locomotion, reduced diameter of skeletal muscle fibers, reduced expression of muscle-specific genes, as well as reduced motoneuron length. The phenotypes in the skeletal muscle, as well as the defect in the motility, were rescued both by microinjection of human ERBB4 mRNA, and by transposon-mediated muscle-specific ERBB4 overexpression. The role of ErbB4 in regulating motility was further controlled by targeted mutation of the endogenous erbb4a locus in the zebrafish genome by CRISPR/Cas9. These observations demonstrate a potential for the ErbB tyrosine kinase inhibitors to induce neuromuscular toxicity in a developing organism via a mechanism involving inhibition of ErbB4 function.